Persuading Voters - Alonso, Ricardo; CÂmara, Odilon (American Economic Review, 2016)
In a symmetric information voting model, an individual (politician) can influence voters' choices by strategically designing a policy experiment (public signal). We characterize the politician's optimal experiment. With a nonunanimous voting rule, she exploits voters' heterogeneity by designing an experiment with realizations targeting different winning coalitions. Consequently, under a simple-majority rule, a majority of voters might be strictly worse off due to the politician's influence. We characterize voters' preferences over electoral rules and provide conditions for a majority of voters to prefer a supermajority (or unanimity) voting rule, in order to induce the politician to supply a more informative experiment. (JEL D72, D83)